Conditions in occupational therapy : effect on occupational performance - Atchison, Ben; Dirette, Diane Powers (Wolters Kluwer/Lippincott Williams & Wilkins, 2012)
This textbook focuses on chronic health problems and their impact on an individual's physical, cognitive, psychological, and social capabilities. Students learn how the patient's age, life tasks, and living environment affect occupational therapy needs, and how to determine what occupational therapy services to provide. Chapters present the etiology, symptoms, prognosis, and progression of conditions frequently encountered in practice. Case studies at the end of every chapter help students apply the content to real-life clinical situations. This edition includes new chapters on vision disorders, muscular dystrophy, infectious diseases, and developmental trauma disorder. The expanded art program includes more photos, drawings, charts, and graphs.